2012
DOI: 10.1039/c2ob26667a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of orientational isomerism in rhodium(ii) metallopeptides by pyrene fluorescence

Abstract: Rhodium(II) metallopeptides display useful secondary structure, self-assembly, and catalytic activity. The bis-peptide complexes exhibit subtle orientational isomerism that affects function, but is challenging to characterize. We report that pyrene excimer fluorescence measurements provide a conclusive proof of isomeric structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Pyrene excimer fluorescence identified Rh 2 L21 2 -isoB as having antiparallel helices. 993 Enantioselectivities from the catalyzed insertion of PhMe 2 SiH into methyl α -diazophenylacetate were improved by 5–18% for four Cbz-protected peptide sequences upon addition of triphenylphos-phite. 994 …”
Section: De Novo Designmentioning
confidence: 99%
“…Pyrene excimer fluorescence identified Rh 2 L21 2 -isoB as having antiparallel helices. 993 Enantioselectivities from the catalyzed insertion of PhMe 2 SiH into methyl α -diazophenylacetate were improved by 5–18% for four Cbz-protected peptide sequences upon addition of triphenylphos-phite. 994 …”
Section: De Novo Designmentioning
confidence: 99%
“…Ball demonstrated a strategy to utilize natural polypeptide ligands for the development of chiral dirhodium catalysts (Scheme 14). 34,35 Based on this strategy, a relatively poor initial "hit" of 45% ee was improved using parallel automated peptide synthesis. In addition, the combined effects of peptide libraries and facile dirhodium complexation proved to be efficient in the development of selective catalytic transformations.…”
Section: Review Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…As part of a program aimed at mimicking the properties of metalloenzymes [6][7][8][9][10] for developing asymmetric transition metal catalysts, [11][12][13] and for rhodium(II) carboxylate complexes in particular, we have demonstrated that peptides with two carboxylate side chains (glutamate or aspartate) serve as chelating ligands 12 for rhodium(II), allowing asymmetric catalytic reactions of diazo compounds. [14][15][16][17] Polypeptides are readily optimizable ligands for stereoselective catalysis owing to the chirality and structural variation present in amino acids. [18][19][20] Our initial efforts 14 developed screening methods that identied bispeptide complexes of the type Rh 2 (peptide) 2 .…”
Section: Introductionmentioning
confidence: 99%